Electoral competition with policy compromise - Gene M. Grossman; Elhanan Helpman (Institute for Advanced Studies (IHS), 1996)
We study the electoral competition between two parties vying for seats in a legislature. The electorate includes knowledgeable voters and impressionable voters, the latter susceptible to electioneering activities. A special interest group provides campaign financing in exchange for influence over the platforms. The parties take positions on two issues, one on which their divergent platforms are fixed and another pliable issue where their announcements are used to woo dollars and votes. The interest group contributes with the knowledge that the final policies will be a compromise between the positions of the two parties.We examine two modes of voting behavior. When knowledgeable voters vote sincerely, the parties' positions on the pliable issue diverge, and the more popular party caters more to the special interest group. When knowledgeable voters vote strategically, the interest group often induces the parties to announce identical pliable platforms. We investigate the determinants of the platforms, contributions, vote counts, and policy compromise, and consider how changes in legislative institutions might affect these outcomes.
Keywords: D72; 330; electoral competition; special interest groups; voting behavior